Research on Genotoxicity Evaluation of the Fungal Alpha-Amylase Enzyme on Drosophila melanogaster - Arzu Taşpınar Ünal; Fahriye Zemheri Navruz; Safiye Elif Korcan; Sinan İnce; Emine Uygur Göçer (Biology)
Alpha-amylase is an extracellular enzyme abundantly produced from fungal sources. The catalytic activity of microbial enzymes is higher, more stable, and economical compared to plant and animal enzymes; they can be produced in large quantities in a short time and do not produce unwanted by-products. In this study, the genotoxic effect of different concentrations (25 mg/mL, 50 mg/mL, and 100 mg/mL) of a native fungal thermostable alpha-amylase enzyme, produced from the Aspergillus niger G2-1 isolate with an enzyme activity of 38.6 U/mg, was investigated on the Drosophila melanogaster model organism. The effect of the alpha-amylase enzyme added to the culture medium on the developmental performance of D. melanogaster was assessed through larval toxicity analysis, its effect on DNA damage through the comet assay, and its response to oxidative stress through various biochemical parameters. As a result, it was determined that low-dose alpha-amylase enzyme concentration (25 mg/mL) did not cause intracellular oxidative stress, did not cause genotoxicity, and did not adversely affect growth performance, although feeding with alpha-amylase at 50 mg/mL and 100 mg/mL concentrations caused a significant decrease in the survival rate of D. melanogaster larvae and an increase in DNA damage rate in imagos. However, oxidative stress parameters in adult D. melanogaster did not change after the same alpha-amylase application.